2019
DOI: 10.1111/maec.12540
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling exploitation of the intertidal grazer Phorcus sauciatus (Gastropoda: Trochidae) in an oceanic archipelago: Implications for conservation

Abstract: Harvesting of intertidal grazers such as topshells is known to affect negatively the exploited populations by altering population structure and decreasing abundance. Phorcus sauciatus has a wide geographic distribution in the North‐eastern Atlantic Ocean and is subject to increasing levels of harvesting pressure due to the expansion of human population on coastal areas. The effect of proximity to human settlements and coastal accessibility on the size structure and abundance of P. sauciatus populations was exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…In this region a negatively allometric growth was obtained, this may result from the high level of harvesting pressure leading to lower population densities and to alterations in population dynamics and size structure (Riera et al 2016;Sousa et al 2018). This is corroborated by the study of Sousa et al (2019) that found a similar pattern of growth, smaller mean size populations and lower proportion of reproductive individuals in this region.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In this region a negatively allometric growth was obtained, this may result from the high level of harvesting pressure leading to lower population densities and to alterations in population dynamics and size structure (Riera et al 2016;Sousa et al 2018). This is corroborated by the study of Sousa et al (2019) that found a similar pattern of growth, smaller mean size populations and lower proportion of reproductive individuals in this region.…”
Section: Discussionsupporting
confidence: 66%
“…Harvesting of keystone species such as topshells negatively affects the exploited populations by altering population structure and decreasing abundance (Sousa et al 2019) and thus the knowledge of species and ecosystems is important to promote the implementation of management measures. Marine Protected Areas (MPAs), defined as no-take zones, are a popular measure for the conservation of harvested marine populations, since they promote the recovery of populations by removing harvesting pressure (Halpern and Warner 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that P. sauciatus from Madeira archipelago exhibited the smallest total length within the four studied locations, this may result from a high level of harvesting pressure, known to negatively affect the exploited populations by altering their population size-structure (Riera et al, 2016;Tuya et al, 2006). Recently, it was suggested that harvesting has a great impact on the population dynamics of P. sauciatus from Madeira archipelago with more emphasis on harvested populations that show a smaller mean size and lower proportion of reproductive individuals (Sousa et al, 2019b).…”
Section: Discussionmentioning
confidence: 61%
“…The differences found between size of harvested and non-harvested populations in mainland Portugal and the Canaries were smaller than those observed in Madeira archipelago. This is related to the lack of regulation in Madeira, with uncontrolled total catch of this species (Sousa et al, 2019b). Also, the lack of widespread traditional harvest of topshells in mainland Portugal results in less marked differences between harvested and non-harvested areas.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being highly exploited since the fifteenth century for human consumption in Madeira, the regional morphological variation of this species is unknown. Most of the studies concerning Phorcus sauciatus from Madeira (NE Atlantic Ocean) have focused on the biological parameters and exploitation rate (Sousa et al, 2019a) and in the effects of harvesting pressure on the size-structure and abundance of populations (Sousa et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%